Influence of composition and size on the thermodynamic stability and structural evolution of CuAlNi nanoclusters - Liu, Qing; Su, Ye; Song, Keke; Wang, Xiaoxu; Gao, Panpan; Wang, Chutian; Xiao, Yuqin; Jian, Xiaodong; Qian, Ping (Progress in natural science, 2020)
The heating process for CuAlNi nanoclusters with cuboctahedral structure was studied by molecular dynamics simulation with the embedded atom method. A diffusionless martensitic transformation from the cuboctahedral (CO) to the icosahedral (ICO) structure before the melting point was found in some CuAlNi nanoclusters. The effects of element composition and cluster size on the thermodynamic stability and structural transformation of trimetallic nanoclusters were investigated. The results show that the CO–ICO transformation temperature was size-dependent and occurred only for small clusters. It was also observed that the CO–ICO transformation temperature firstly dropped and then raised as Al concentration increased, which may be strongly related to the release of excess energy. Furthermore, the surface segregation phenomenon was also observed that the lower surface energy components, such as Al and Cu atoms, segregated to the surface of CuAlNi nanoclusters. The changes in the melting points of CuAlNi nanoclusters with different alloy compositions and cluster sizes were also studied. And furthermore, the physical basis of structural transition of CuAlNi nanoclusters was discussed. [Display omitted] •CuAlNi nanoclusters undergo a martensitic transformation from the cuboctahedral to the icosahedral structure before melting.•The icosahedral transformation temperature is strongly related to the release of excess energy.•The melting point of CuAlNi nanoclusters decreases as Al concentration increases, and increases as cluster size increases.